Can farmers reliably perform neonatal lamb post mortems and what are the perceived obstacles to influencing lamb mortality? - Gascoigne, Emily; Bazeley, Katrine; Lovatt, Fiona (Elsevier, 2017)
Neonatal lamb mortality constitutes a significant economic cost and is an important welfare challenge. Despite compelling evidence for reduction strategies and cost benefits associated with them, there has been no documented reduction in mortality since the 1970’s. We aimed to evaluate whether a knowledge exchange solution could be used to define farm specific loss risks accurately. This was done by training farmers how to examine neonatal lambs post-mortem to record and interpret common causes of mortality by following a basic framework. We used participatory rural appraisal to assess some of the existing challenges to reducing lamb mortality. When considering outcomes for specific post mortem questions, there was 87.5% agreement between veterinary and farmer answers and 82.3% of farmer diagnoses (n = 96) agreed with the veterinary conclusions. When merged with farmer performed post-mortems, farm specific mortality pie-charts were developed to highlight the variation between flocks and the necessity for flock specific advice. Common challenges to reducing lamb loss included level of labour, skill set of labour, communication within teams and whether farmers generally considered post-mortems to be a valuable tool. We consider that farmer post-mortems of lambs could be a tool for the veterinary-farmer team, facilitating the communication of farm specific advice and empowering farmers to effect positive change.